Application of Statistical Quality Control and Failure Mode and Effect Analysis to Improve Panada Tore Quality at PT. Cita Rasa Pagimana - Kudo, Syafri Yandi; Isa, Dewi Rahmawaty; Payu, Muhammad Rezky Friesta (Journal of Mathematics, Computations and Statistics, 2025)
The manufacturing industry in Banggai Regency, Indonesia, is growing rapidly and is the main sector supporting PDRB. PT Cita Rasa Pagimana, a producer of Pagimana's signature panada tore, faces product quality problems such as charring and crumbling despite clear production standards, causing losses due to the large number of defective products. This study aims to implement a combination of Statistical Quality Control (SQC) method with Seven Tools and Failure Mode and Effect Analysis (FMEA) to identify the causes and resolve panada tore production defects. The results showed 6.680 defective products out of 189.590 products in December 2024, with charred defects accounting for 64% (4.393 products) and crumbled defects 36% (2.287 products). Based on FMEA, the five main causes with the highest RPN are: inconsistent frying technique, absence of oil thermometer, improper dosage of raw materials, overheating room temperature, and rough handling of dough. Recommendations for improvement include training on frying techniques, providing an oil temperature thermometer, adjusting the dosage of raw materials, adjusting the room temperature, and periodic training to improve employees' understanding of the production process, which is expected to reduce defects and improve product quality.